The Effectiveness of Spiritual Psychotherapy on Patients with Mental Disorders: A Systematic Review - Ahmad Wahyudi; Ah Yusuf; Mundakir (Poltekkes Kemenkes Palu, 2021)
Recently, the research analyzes the relationship between religion and spirituality has grown rapidly.Many mental health clinics have implemented interventions on religious and spirituality-based mental disorders. This article aimed to examine the effectiveness of handling mental-based mental disorders from various studies that have been conducted. Methods: The articles used in this systematic review were searched in the SCOPUS, PROQUEST, SPRINGERLINK, SAGE and SCIENCEDIRECT databases which is published between 2016-2020. The keyword used were